2010
DOI: 10.1590/s1519-69842010000500009
|View full text |Cite
|
Sign up to set email alerts
|

Germination and initial growth of Campomanesia xanthocarpa O. Berg. (Myrtaceae), in petroleum-contaminated soil and bioremediated soil

Abstract: In 2000 there was an oil spill at the Getúlio Vargas Refinery (REPAR) in Paraná. Nearly five years after contamination and the use of bioremediation, a study was carried out to identify the effects of the contaminated soil and the bioremediated soil on the germination and initial growth of C. xanthocarpa. The experiment was established with soil from REPAR, with three treatment groups: contaminated soil (C), bioremediated soil (B) and uncontaminated soil (U); with five repetitions of 50 seeds each. There was n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 19 publications
0
6
0
5
Order By: Relevance
“…Henner et al (1999) reported that petroleum hydrocarbons consisting of small molecules and those that are water soluble are more phytotoxic for the germination. However, there have been reports describing the species whose germination was not affected by the presence of oil in the ground (Adam and Duncan, 2002;Merkl et al, 2004;Gogosz et al, 2010). The symptoms caused by the contamination with oil are countless and are generally not specific.…”
Section: Introductionmentioning
confidence: 99%
“…Henner et al (1999) reported that petroleum hydrocarbons consisting of small molecules and those that are water soluble are more phytotoxic for the germination. However, there have been reports describing the species whose germination was not affected by the presence of oil in the ground (Adam and Duncan, 2002;Merkl et al, 2004;Gogosz et al, 2010). The symptoms caused by the contamination with oil are countless and are generally not specific.…”
Section: Introductionmentioning
confidence: 99%
“…Gogosz et al (2010) As altas taxas de germinação tanto na luz quanto no escuro podem contribuir para explicar a ocorrência da espécie tanto em ambientes com bastante luz disponível, como nas orlas das florestas (LEGRAND; KLEIN, 1970), quanto no sub-bosque das formações florestais, onde frequentemente ocorre (CARMO; MORELLATO, 2000). A independência de luz para germinação foi constatada por Rego (2010), para M. gertii, e por Santos et al (2004), para C. xanthocarpa, enquanto que algumas outras espécies de Myrtaceae analisadas (A. sellowiana, M. pungens e P. cattleyanum) parecem ter fotoblastia positiva, com menores percentuais de germinação no escuro.…”
Section: Discussionunclassified
“…Portanto, a análise da germinação de sementes é base para a propagação de espécies nativas e para o entendimento da regeneração natural em comunidades vegetais. Alguns autores têm estudado aspectos tecnológicos e/ou ecomorfológicos do processo germinativo em espécies nativas de Myrtaceae: Gogosz et al (2010Gogosz et al ( , 2015, Gomes et al (2016), Rego et al (2009Rego et al ( , 2010Rego et al ( , 2011), e Santos et al (2015).…”
Section: Introductionunclassified
“…The relative frequency of germination (behaviour of the seeds in the germination process over time) was calculated using the equation (Gogosz et al, 2010):…”
Section: Methodsmentioning
confidence: 99%